1998
DOI: 10.1007/s100380050064
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of chromosome 7q in a patient with Williams syndrome and infantile spasms

Abstract: Interstitial deletion of 7q11.23-q21.11 was identified by cytogenetic methods in a 4-year-old boy with Williams syndrome (WS) and infantile spasms. Deletion of the elastin (ELN) gene and the DNA polymorphic markers, D7S1870, D7S2490, D7S2518, and D7S2421, were identified in the patient, but the loci for D7S653 and D7S675 were not involved. Zackowski et al. (1990) reported that 6 of 16 patients with the interstitial deletion of 7q11.2-q22 had abnormal electro encephalograms, or seizures, or both, and that infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
0
31
1
2
Order By: Relevance
“…The hypotonia noted in young children typically improves in childhood (Chapman et al 1996). Seizures are relatively rare aVecting <10% of individuals with WBS (Amenta et al 2005), and there are few reports of children with infantile spasms and hypsarrhythmia, usually associated with larger 7q11.23-q21.2 deletions involving the MAGI2 gene (Mizugishi et al 1998;Morimoto et al 2003;Trauner et al 1989;Tsao and Westman 1997).…”
Section: Neurological Problemsmentioning
confidence: 96%
“…The hypotonia noted in young children typically improves in childhood (Chapman et al 1996). Seizures are relatively rare aVecting <10% of individuals with WBS (Amenta et al 2005), and there are few reports of children with infantile spasms and hypsarrhythmia, usually associated with larger 7q11.23-q21.2 deletions involving the MAGI2 gene (Mizugishi et al 1998;Morimoto et al 2003;Trauner et al 1989;Tsao and Westman 1997).…”
Section: Neurological Problemsmentioning
confidence: 96%
“…Up to now it has not been possible to associate the presence of the WBS as the underlying cause of WS, although other cases showing both WBS and WS have been reported [Kahler et al, 1995;Tsao & Westman, 1997;Mizugishi et al, 1998]. …”
Section: To the Editormentioning
confidence: 98%
“…Three genes-MAGI2 (MIM: 606382), HIP1 (MIM: 601767), and YWHAGhave been suggested as possible candidates for these atypical features. [46][47][48][49][50][51][52][53] Ramocki et al 51 suggested that haploinsufficiency of HIP1 is sufficient to alter neuronal homeostasis and cause focal and generalized epilepsies and cognitive dysfunction. However, their findings do not exclude the possibility that YWHAG loss of function is sufficient to cause neurological phenotypes alone, as proven by our results.…”
mentioning
confidence: 99%